(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The principle that public associations are an important part of the state and society, and they also act as a link between the state and the individual, is enshrined in the concept of the rule of law and civil society. Therefore, state and social development are closely related to these civil institutions, as they determine the improvement and development of democracy. These opinions are not secret to anyone today, since they are important, integral elements of civil society and the rule of law. Today, thousands of civil associations and unions exist and work constructively in all states. But not all of them are focused on defending the real interests of people, and this state of affairs hinders the development of civil society.